Planning scenarios for improving the performance of education personnel after COVID-19 at XYZ University - Suryanto, Yustinus Ricky Hapsoro (Indonesian Journal of Multidisciplinary Science, 2024)
In the post-Covid-19 pandemic period with such rapid changing dynamics, the role of education personnel in the university environment is increasingly crucial to support the development and improvement of education quality. The purpose of this study is to identify and analyze internal and external factors that affect the performance of XYZ University education personnel and determine scenario planning to improve the performance. The results of this research show that there are four scenarios that can occur based on the planning scenario matrix, namely scenarios in optimistic, semioptimistic, semi-pessimistic and pessimiistic conditions. It can be concluded that the current condition of the condition of organizational aspects is in an optimistic scenario, in this case the organization facilitates and aspects of educational personnel that support efforts to improve performance, so that the formulation of strategies carried out by the company focuses on optimistic scenarios where the company can implement hybrid work methods supported by clear and well-socialized regulations to education staff and supported by optimizing the function of HRM applications and strengthening the ability of education staff to carry out their job responsibilities, especially online.